1991
DOI: 10.1111/j.1467-9604.1991.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Hands on: Computer experience and the child with special educational needs

Abstract: Dolores Loughrey takes a refreshing look at the use of computers in special educational settings. Many of her arguments have been deployed before but it is encouraging to have further confirmation of those beliefs. The use of computer technology still has a long way to go and is far from being a standard tool of special needs educators. Perhaps the sense of fun and excitement that creeps into this article will entice others into this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Computer-centred group work can offer a suitable environment: while children may engage in verbal and non-verbal tasks, the computer provides a third party focus which may alleviate pressure on the child with ASD to interact directly with peers. Gross (1996) and Loughrey (1991) conducted studies of children with special educational needs (SEN) which found that being involved in collaborative work increased the status of a child with SEN providing that they played a key role in a special project in which they could be successful. Loughrey (ibid.,p.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-centred group work can offer a suitable environment: while children may engage in verbal and non-verbal tasks, the computer provides a third party focus which may alleviate pressure on the child with ASD to interact directly with peers. Gross (1996) and Loughrey (1991) conducted studies of children with special educational needs (SEN) which found that being involved in collaborative work increased the status of a child with SEN providing that they played a key role in a special project in which they could be successful. Loughrey (ibid.,p.…”
Section: Introductionmentioning
confidence: 99%